2010
DOI: 10.1111/j.1525-1446.2010.00918.x
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Mask Wearing for Influenza‐like Illnesses Among Urban Hispanic Households

Abstract: Face masks may not be an effective intervention for seasonal or pandemic influenza unless the risk perception of influenza is high. Dissemination of culturally appropriate mask use information by health authorities and providers must be emphasized when educating the public.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
53
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 27 publications
5
53
0
Order By: Relevance
“…However, given the lower reported compliance in the N95 group, if noncompliance was higher than reported, this would drive the trial results toward the null, which means the true difference between the interventions may be greater than that observed. Acceptability of face mask use in developed country settings is lower than in Asian countries (39), and this limits the translation of the findings. We previously determined that running this trial in Australia would be unfeasible because of low compliance (40).…”
Section: Discussionmentioning
confidence: 96%
“…However, given the lower reported compliance in the N95 group, if noncompliance was higher than reported, this would drive the trial results toward the null, which means the true difference between the interventions may be greater than that observed. Acceptability of face mask use in developed country settings is lower than in Asian countries (39), and this limits the translation of the findings. We previously determined that running this trial in Australia would be unfeasible because of low compliance (40).…”
Section: Discussionmentioning
confidence: 96%
“…Although the effectiveness of wearing a face mask for preventing infectious diseases has been investigated in various other studies [5,7,9,10,19,20], most have not considered possible associations between wearing a face mask and additional hygiene practices. However, we should note that a randomized controlled study which allocated face masks only revealed no statistically significantly differences in hand hygiene practices [8].…”
Section: Discussionmentioning
confidence: 99%
“…Wearing a facemask as well as adopting positive hand hygiene practices has been shown to reduce respiratory illness in shared living settings among young adults [8,9] with a relatively high compliance when wearing a mask. However, some other research has shown that compliance when wearing a face mask is low, especially in non-randomized studies [10,11]. …”
Section: Introductionmentioning
confidence: 99%
“…In the case of the recent influenza H1N1 pandemic, for instance, the disease was given wide media coverage and it received a great deal of attention by public and health authorities that resulted in greater risk perception worldwide (20,21). Conversely, poor knowledge has been shown to be a risk factor for low risk perception and hence non-adherence to general precautions recommended by health authorities (22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%